1997
DOI: 10.1093/molehr/3.10.839
|View full text |Cite
|
Sign up to set email alerts
|

Use of mannose ligands in IVF screens to mimic zona pellucida-induced acrosome reactions and predict fertilization success

Abstract: A predictive test for determining whether motile populations of human spermatozoa will fertilize eggs in vitro has been an elusive goal of clinical research. We have developed an assay for the ability of motile human spermatozoa to bind fluorescein isothiocyanate-labelled mannosylated bovine serum albumin (Man-FITC-BSA) as a test for the presence of sperm surface receptors (lectins) for mannose ligands. Mannosylated ligands are present on the human zona pellucida and are involved in the species-specific bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…Note that expression of all biomarkers tested correlates with the rate of fertilization in IVF (58,60,67,69).…”
Section: Sperm Function Testingmentioning
confidence: 91%
See 1 more Smart Citation
“…Note that expression of all biomarkers tested correlates with the rate of fertilization in IVF (58,60,67,69).…”
Section: Sperm Function Testingmentioning
confidence: 91%
“…The increase in premature ("spontaneous") acrosome loss upon capacitation (60) and the ability of capacitated sperm to undergo acrosome loss induced by exposure of sperm to model zona ligands containing mannose (67) or to 1 μg/mL progesterone (68,69) were assessed by labeling of acrosome content with rhodamine-labeled Pisum sativum agglutinin (70). Labeled sperm were viewed at 600× magnification with an Olympus BX-50 UV-epifluorescence microscope (Olympus, Lake Success, NY, USA).…”
Section: Sperm Function Testingmentioning
confidence: 99%
“…Cadmium is absorbed via the lungs in significant quantities from cigarette smoke and it has toxic effects on the male reproductive system [2][3][4][5] which may account for the recent declining fertility in men in developed countries. The role of cadmium in the modulation of male reproductive health stems from the observations that high levels of cadmium in seminal fluid are associated with asthenozoospermia in infertile males [6]. Furthermore, animal studies demonstrated a time-and dose-dependent reduction in sperm motility following cadmium exposures [7].…”
Section: Introductionmentioning
confidence: 99%
“…Neoglycoproteins containing mannose or N-acetylglucosamine residues induce the human sperm AR, with requirements similar to those of the zona pellucida (5). The NGP effect occurs by signal transduction pathways similar to those described for zona-induced AR, i.e., activation of G-proteins, voltage-dependent calcium channels (26) and tyrosine kinase (6). The induction of AR by GlcNAcneoglycoprotein also presents a positive correlation with in vitro fertilization rates (9).…”
Section: Discussionmentioning
confidence: 86%
“…Binding sites for mannose and N-acetylglucosamine have been proposed to play an important role in human fertilization. They are involved in the induction of AR by N-acetylglucosamine-and mannose-containing neoglycoproteins (NGP) (5)(6)(7) and are related to the fertilizing potential of spermatozoa (8)(9)(10). Moreover, the stimulation of human sperm AR by neoglycoproteins is strongly correlated with the rate of fertilization in vitro (9,10), and may be used to predict fertilization success.…”
Section: Introductionmentioning
confidence: 99%